Melampaui Lembaga Formal: Menjelaskan Kinerja Bumdes melalui Akuntabilitas, Transparansi, Partisipasi, dan Kepatuhan Regulasi - Rolis Lasido; Muchtar Ahmad; Alfiah Agussalim; Yakob Noho Nani; Muchlis Akuba (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
Village-Owned Enterprises (BUMDes) have become an important instrument in promoting rural economic development in Indonesia by strengthening local economic potential and improving community welfare. Although BUMDes operate under relatively similar regulatory frameworks and institutional arrangements, their organizational performance varies considerably across regions. Previous studies have primarily emphasized managerial, financial, and entrepreneurial factors, while limited attention has been given to governance mechanisms that connect formal institutions with organizational performance. This study aims to analyze how accountability, transparency, community participation, and regulatory compliance influence the performance of BUMDes in Molosipat Village, South Bolaang Mongondow Regency. A qualitative case study approach was employed, with data collected through in-depth interviews, direct observations, and document analysis involving village government officials, BUMDes managers, and community representatives. The findings reveal that governance functions as a mechanism linking formal institutional arrangements to organizational performance. Accountability strengthens organizational discipline and responsibility, transparency increases public trust, community participation encourages collective support and stakeholder involvement, while regulatory compliance promotes institutional stability and operational consistency. These governance mechanisms collectively enhance the effectiveness and sustainability of BUMDes management. The study concludes that organizational performance is determined not merely by the existence of formal institutions but by the quality of governance practices implemented within them. This research contributes to governance theory by demonstrating how governance mechanisms mediate the relationship between institutional structures and organizational outcomes in community-based public organizations.